Cytosolic dsRNA sensors as regulators of transgene expression from AAV vectors in human iPSC-derived cardiomyocytes. (3rd October 2022) - Kraszewska, I; Jazwa-Kusior, A; Dulak, J
Abstract: Background: Adeno-associated viral vectors (AAVs) are safe and efficient tools for delivery of therapeutic genes in numerous applications. Although they elicit only limited immune response in host cells, a recent study has demonstrated an association between decreasing transgene expression in the liver and induction of the immune response to cytoplasmic dsRNA. While AAVs are DNA vectors, it appears that their unique genome structure allows the generation of dsRNA in transduced cells. Since the expression cassette is flanked by inverted terminal repeats (ITRs), which can function as bidirectional promoters, assembly of sense and antisense transcripts can potentially result in formation of dsRNA structures, especially in cells exhibiting high transgene expression. Purpose: In this study, we explored the mechanism of dsRNA recognition in cardiomyocytes, to unravel its role in the regulation of transgene expression from AAV vectors. Methods: For this purpose, we utilised human iPSC-derived cardiomyocytes transduced with self-complementary AAV6 or AAV9 vectors encoding GFP. Since we focused on the long-term effects of transgene expression, all the analyses were performed 7–9 days after AAV transduction. Results: We confirmed that ITR serves as a functional promoter in the cells, capable of maintaining approximately half of the fluorescence signal compared to the CMV promoter. Long-term transgene expression was associated with elevated expression of dsRNA sensors (MDA5, RIG-I, LGP2 and TLR3) and the appearance of small foci of dsRNA in the perinuclear region. Unlike an artificial ligand for dsRNA sensors, poly (I:C), dsRNA in AAV-transduced cells did not interact with the LGP2 protein. To induce dsRNA recognition, we stimulated the cells with IFNβ for 1 week, starting from day 1 after transduction. We found that transgene expression is significantly hampered in such conditions. Furthermore, IFNβ induced the direct interaction of dsRNA with the OAS1 protein in transduced cells. During viral infections, OAS1 and its effector nuclease RNAse L promote the degradation of mRNA to restrict the production of viral proteins. Since RNAse L is not specific for particular transcripts, we hypothesize that activation of the OAS1 pathway in transduced cells is responsible for downregulation of transgene expression. While IFNβ induced OAS1-dsRNA recognition, we did not observe such an event in cells transduced with AAV and maintained under standard conditions. In turn, AAV transduction resulted in a reduction in OAS1 expression at the mRNA and protein level, suggesting a possible reason for tolerance to dsRNA in transduced cardiomyocytes. Conclusions: Our data present a novel mechanism of regulation of transgene expression in AAV-transduced cells involving OAS1–RNAse L pathway and provide deeper insight into the general signal transduction routes activated in response to cytosolic dsRNA in human iPSC-derived cardiomyocytes. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Centre - PRELUDUM grant 2019/33/N/NZ1/03066Jagiellonian University, Faculty of Biochemistry, Biophysics and Biotechnology - grant for young scientists MNS 6/2020